Elatsoe ebook - Badger, Darcie Little (2020)
A National Indie Bestseller TIME's Best 100 Fantasy Books of All Time An NPR Best Book of 2020 A Booklist's Top 10 First Novel for Youth A BookPage Best Book of 2020 A CPL "Best of the Best" Book A Publishers Weekly Best Book of 2020 A Buzzfeed Best YA SFF Book of 2020 A Shelf Awareness Best Book of 2020 An AICL Best YA Book of 2020 A Kirkus Best YA Book of 2020 A Tor Best Book of 2020 PRAISE "Groundbreaking." —TIME "Deeply enjoyable from start to finish." —NPR "Utterly magical." —SyFyWire "Atmospheric and lyrical...a gorgeous work of art." —BuzzFeed "One of the best YA debuts of 2020. Read it." —Marieke Nijkamp FIVE STARRED REVIEWS ★ "A fresh voice and perspective." —Booklist, starred review ★ "A unique and powerful Native American voice." —BookPage, starred review ★ "A brilliant, engaging debut." —Kirkus Reviews, starred review ★ "A fast-paced murder mystery." —Publishers Weekly, starred review ★ "A Lipan Apache Sookie Stackhouse for the teen set." —Shelf-Awareness, starred review A Texas teen comes face-to-face with a cousin's ghost and vows to unmask the murderer. Elatsoe—Ellie for short—lives in an alternate contemporary America shaped by the ancestral magics and knowledge of its Indigenous and immigrant groups. She can raise the spirits of dead animals—most importantly, her ghost dog Kirby. When her beloved cousin dies, all signs point to a car crash, but his ghost tells her otherwise: He was murdered. Who killed him and how did he die? With the help of her family, her best friend Jay, and the memory great, great, great, great, great, great grandmother, Elatsoe, must track down the killer and unravel the mystery of this creepy town and its dark past. But will the nefarious townsfolk and a mysterious Doctor stop her before she gets started? A breathtaking debut novel featuring an asexual, Apache teen protagonist, Elatsoe combines mystery, horror, noir, ancestral knowledge, haunting illustrations, fantasy elements, and is one of the most-talked about debuts of the year.